Puérperas adolescentes: conhecimentos e práticas em aleitamento materno - SILVA, Luciana da (2023)
Objective: To analyze the knowledge and practice of adolescent mothers on the importance of breastfeeding according to criteria of the Baby Friendly Hospital Initiative. Methods: This is an observational, descriptive and quantitative study conducted in the joint housing of a public hospital located in the city of Belém, Pará. The target population consisted of adolescent postpartum women. In the data collection, a structured form was used based on the 10 steps for the success of Breastfeeding, which defines the criteria for the full functioning of the Baby Friendly Hospital Initiative. RESULTS: The age of 17 years corresponds to 40% of the sample, 62% were from the interior of Pará, 51% had 0 to 8 years of schooling, 53% of the interviewees had a normal birth, 87% of the mothers were primiparous. About prenatal care 72% of adolescents had 6 or more consultations and 51% reported having received guidelines on breastfeeding during prenatal care. The majority of mothers (57%) reported that the baby was put on skin-to-skin contact in the first hour of life, 64% reported needing help from a professional in the hospital to breastfeed, and 98% of the mothers were satisfied with the professional breastfeeding support from the hospital. A proportion of 62% of the infants were exclusively breastfed, receiving no supplement and 100% of the mothers affirmed any type of artificial nozzle offer to their child. As for the signs of identification of the need to put the baby to breastfeed, 60% revealed that they placed it to the breast with the crying signal. Conclusion: Primiparity, schooling and type of delivery were observed as factors that discouraged the practice of breastfeeding.